Keterwakilan Politik Perempuan Melalui Keterpilihan Anggota Legislatif Perempuan Pada DPRD Kabupaten Bogor Pada Tahun 2014-2019 - Bina Aprianis Bu’ulolo (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2021)
The fulfillment of women's political representation in the Regional House of Representatives (DPRD) of Bogor Regency is still an unresolved problem. This is due to the fact that the quota for women's seats has never been fulfilled as mandated by the Law on General Elections. The obstacles that make it difficult to fulfill the 30 percent quota for women's political representation in the Bogor Regency DPRD are also various. One of them, because women do not control the political structure and live in a patriarchal society. This has prevented women from taking part in politics and taking part in policy making. This study raises the issue of the factors causing the minimal number of women in the Bogor Regency legislature for the 2014-2019 and 2019-2024 periods. Using qualitative research methods, the focus of this research lies on the minimal number of women in the Bogor Regency DPRD and their function in making policy for women. Data collection techniques used in this research, namely observation and interviews. The results of the study show that the political representation of women in the legislature is still very low in quantity. This is evidenced by the fact that for two periods, the number of members of the Bogor Regency DPRD was never more than five people, while the number of male representatives was almost 95 percent of the total 55 seats. This condition makes many women's problems have not been accommodated properly. In fact, during these two periods, the DPRD and the Bogor Regency government only produced two Regional Regulations that accommodated the interests of women